Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy IX 2018
DOI: 10.1117/12.2312971
|View full text |Cite
|
Sign up to set email alerts
|

Systematic uncertainties in the Simons Observatory: optical effects and sensitivity considerations

Abstract: The Simons Observatory (SO) is a new experiment that aims to measure the cosmic microwave background (CMB) in temperature and polarization. SO will measure the polarized sky over a large range of microwave frequencies and angular scales using a combination of small (∼0.5 m) and large (∼6 m) aperture telescopes and will be located in the Atacama Desert in Chile. This work is part of a series of papers studying calibration, sensitivity, and systematic errors for SO. In this paper, we discuss current efforts to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…For this purpose, and to construct sky maps from the simulated TOD, we use the public Python package s4cmb 1 [14]. This software, which is derived from the POLARBEAR data analysis systematics pipeline, has been used to perform a preliminary systematics study for SO [10,15,16], and to explore the effects of systematics on B-mode measurements on real data [7,17]. Injecting systematics directly into the simulated detector-by-detector TOD allows us to explore a wider set of systematics in a more realistic way than other possible treatments of systematics (such as effective induced map-domain systematics), and includes their variation across the focal plane of the instrument.…”
Section: Instrumental Systematics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, and to construct sky maps from the simulated TOD, we use the public Python package s4cmb 1 [14]. This software, which is derived from the POLARBEAR data analysis systematics pipeline, has been used to perform a preliminary systematics study for SO [10,15,16], and to explore the effects of systematics on B-mode measurements on real data [7,17]. Injecting systematics directly into the simulated detector-by-detector TOD allows us to explore a wider set of systematics in a more realistic way than other possible treatments of systematics (such as effective induced map-domain systematics), and includes their variation across the focal plane of the instrument.…”
Section: Instrumental Systematics Simulationsmentioning
confidence: 99%
“…In our simulations, we do not model the cross-polar beam response. This response is expected to be subdominant for an SO-like instrument based on modern optical coupling technologies for bolometric detectors and cross-Dragone telescopes [10,15]. We also assume that all baseline beams have a perfect circular shape with a Gaussian radial profile.…”
Section: A Beam Ellipticitymentioning
confidence: 99%
“…Note however that this accounts only for the wavefront errors due to the optics -manufacturing and alignment errors are not included. Given that one obvious application of this very large field of view would be for observations of CMB polarization, an investigation of the polarization properties of the modified design was conducted in GRASP 22 and is discussed in Gallardo et al 2018. It was found that the shaping maintains the very low cross polarization intrinsic to the Dragone design.…”
Section: Coma Correctionmentioning
confidence: 99%
“…A CCAT first-light camera design is discussed in Vavagiakis et al 2018 7 . An SO science book is in development, an overview of SO instrumentation is presented in Galitzki et al 2018 8 , optical systematics for this telescope design are described in Gallardo et al 2018 9 , cryogenic optics designs are in Dicker et al 2018 10 , and design analyses for the SO LAT receiver are presented in Zhu et al 2018 11 , Orlowski-Scherer et al 2018 12 , and Coppi et al 2018 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The LAT has a 6 m-diameter primary mirror, a 7.8 degree FOV, and up to 13 cameras in a 2.4 m diameter receiver that cover more than a decade in frequency. 15,41,43 Motivated by the immensity and complexity of the LAT system, effort has been devoted to understanding and controlling ambient-temperature spillover and scattering, 40 as minimizing optical loading is critical to maintaining low NEP ph . Figure 6 shows relative in-band optical power and MS in each frequency band as a function of LAT primary spillover fraction.…”
Section: Lat Primary Spillovermentioning
confidence: 99%